1995
DOI: 10.1016/0370-2693(94)01534-j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal equilibration and expansion in nucleus-nucleus collisions at the AGS

Abstract: The rather complete data set of hadron yields from central Si + A collisions at the Brookhaven AGS is used to test whether the system at freeze-out is in thermal and hadro-chemical equilibrium. Rapidity and transverse momentum distributions are discussed with regards to the information they provide on hydrodynamic flow.The goal of the ultra-relativistic heavy-ion program at the BNL AGS and CERN SPS is to study highly excited and dense nuclear matter and possibly the transition from hot and dense hadronic matte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
630
3
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 576 publications
(677 citation statements)
references
References 30 publications
42
630
3
2
Order By: Relevance
“…Such hypothesis is well confirmed by the experimental data and adopted in many theoretical works [13,14,15]. A crucial rôle in the solution of the above NLFPE plays the choice of the diffusion and the drift coefficients.…”
Section: Rapidity Distribution In Relativistic Heavy-ion Collisionssupporting
confidence: 66%
See 1 more Smart Citation
“…Such hypothesis is well confirmed by the experimental data and adopted in many theoretical works [13,14,15]. A crucial rôle in the solution of the above NLFPE plays the choice of the diffusion and the drift coefficients.…”
Section: Rapidity Distribution In Relativistic Heavy-ion Collisionssupporting
confidence: 66%
“…Rapidity spectra calculated from (58) will ultimately depend on two parameters: the "interaction" time τ = γt and the non-extensive parameter q. Therefore, no more free parameters are used in this analysis respect to previous theoretical studies [14,15]. The obtained spectra are normalized to 164 protons and the beam rapidity is fixed to y cm = 2.9 (in the c.m.…”
Section: Rapidity Distribution In Relativistic Heavy-ion Collisionsmentioning
confidence: 99%
“…The SHARE LHC freeze-out temperature is clearly below the lattice critical temperature range. The results of other groups are obtained with simplified parameter sets: marked GSI [80,81], Florence [82][83][84], THERMUS [85], STAR [86] and AL-ICE [87,88]. These results show the chemical freeze-out temperature T in general well above the lattice T H .…”
Section: Why Value Of T H Matters To Shm Analysis?mentioning
confidence: 99%
“…This complete set is necessary since the observed particle set includes particles arising from [71,72], the SHM-SHARE results (full circles) [7,[73][74][75][76][77][78][79] and results of other groups [80][81][82][83][84][85][86][87][88]. Figure from ref.…”
Section: Datamentioning
confidence: 99%
“…Turning to more detailed information on hadron production we note that hadron yields observed in central nuclear collisions at AGS, SPS, and RHIC energies are found to be described with high precision within a hadro-chemical equilibrium approach [15,16,17,18,19,20,21,22,23], governed by a chemical freeze-out temperature T ch , baryo-chemical potential µ and the fireball volume V ch . A recent review can be found in [24].…”
Section: Hadron Production and The Qcd Phase Boundarymentioning
confidence: 99%